BUCKLING OF PLATES SUBJECTED TO ROTATION-DEPENDENT LOADS - Abreu, Rafael Henrique Viana; Rosas e Silva, Raul (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper studies the buckling of thick plates subjected to loads which depend on the deformation of the structures, more specifically on the rotations about in-plane axes. In the cases studied in the paper the applied forces are not derivable from a potential function (nonconservative loading). The numerical model is a version of the Rayleigh-Ritz method, with appropriate global functions, with addition of nonsymmetrical matrices which statically simulate the load dependence on rotations. Special attention is given to the effect of shear deformation in the flutter load. It is confirmed that the dynamic buckling load is more affected by shear than the static buckling load, due to the modal interaction. A peculiar behavior is also observed in the case of an unusual loading which does not introduce primary in-plane forces in the plate. Examples of rectangular plats with different boundary conditions are presented.